The Influence of Work Environment and Leadership on Employee Performance with Job Satisfaction as a Moderator Variable at PT. Citra Indah Pertiwi - Warista, Arif; Siregar, Zulkifli Musannif Efendi; Halim, Abdul (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2022)
This research aims to answer the influence of the work environment and leadership on employee performance with job satisfaction as a moderator variable at PT. Citra Indah Pertiwi. Data collection was carried out by distributing questionnaires to PT. Citra Indah Pertiwi, totaling 43 people. This research uses quantitative methods and carries out data processing using the IBM SPSS Statistics 22 tool. This analysis includes reliability tests, validity tests, classical assumption tests, statistical tests, multiple linear regression tests, and moderation tests using Moderated Regression Analysis (MRA). The results of the t-test (partial) show that the work environment has a positive and significant effect on employee performance with a coefficient value of 0.203 a probability value of 0.003 and a calculated t-value of 3.725. Leadership has a positive and significant effect on employee performance with a coefficient value of 0.108 with a probability value of 0.000 and a calculated t value of 2.367. Meanwhile, the results of the f (simultaneous) test show a value of 13.387, which means that the work environment and leadership together have a significant influence on employee performance. The results of the multiple linear tests show the results Y= 14.881+0.203X1+0.108X2. Job satisfaction can moderate the influence of the work environment and leadership on employee performance.